2022
DOI: 10.1002/adom.202200522
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Mechanism of the Persistent Photoconductivity in InSe and its Doped Counterparts

Abstract: The ORCID identification number(s) for the author(s) of this article can be found under https://doi.org/10.1002/adom.202200522.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Trapped states in semiconductors, commonly introduced by defects or dopants, can capture photogenerated electrons or holes under illumination, resulting in an extended lifetime of photogenerated carriers. 41,43…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Trapped states in semiconductors, commonly introduced by defects or dopants, can capture photogenerated electrons or holes under illumination, resulting in an extended lifetime of photogenerated carriers. 41,43…”
Section: Resultsmentioning
confidence: 99%
“…Trapped states in semiconductors, commonly introduced by defects or dopants, can capture photogenerated electrons or holes under illumination, resulting in an extended lifetime of photogenerated carriers. 41,43 By comparing the performance of the two devices, the high carrier separation capability and more trap states of the MoS 2 :Er-based device are considered to be the main reasons for the ISDC phenomenon, as illustrated in Fig. 6(a).…”
Section: Resultsmentioning
confidence: 99%
“…In general, controlling dopants and their concentrations can augment the performance of photodetectors and enable multifunctionality since dopant-induced trap states are essential in determining the optoelectrical properties of semiconductors. Recently, Liao et al 175 reported the performance of an InSe photodetector based on Ge and Sn-doped InSe, revealing the mechanism of persistent photoconductivity in InSe. Photogenerated carriers are trapped in Ge or Sn shallow impurity states, improving the optoelectrical performance of pristine InSe.…”
Section: Inse Optoelectronic Devicesmentioning
confidence: 99%
“…(j-l) Illumination dependence (j) responsivity (R), (k) detectivity (D*) of as-prepared pure InSe, InSe (Ge), and InSe (Sn) photodetector measured under the applied bias of 1 V, (l) power dependence of photoconductive gain. Reproduced with permission 175. Copyright 2022, Wiley-VCH.…”
mentioning
confidence: 99%
“…The phenomenon of PPC has been observed in a wide range of materials. Scientists have observed the PPC phenomenon in various material systems, including complex alloys like AlGaAs and Cu 2 ZnSn 4 , metal oxides such as zinc oxide (ZnO), In 2 O 3 , InGaZnO, gallium oxide (Ga 2 O 3 ), titanium dioxide (TiO 2 ), Hf–Zn–O, BaSnO 3 , and BiFeO 3 (BFO), superconductors like YBa 2 Cu 3 O 6+ x , two-dimensional (2D) materials such as MoS 2 and MoS 2 –WS 2 heterostructures, and other semiconductors like GaN, 2H-MoSe 2 , 4H-SiC, Si nanomembrane, InP, SrTiO 3 , , organic memory phototransistors, and InSe, among others. Due to the adverse impact of the PPC effect on the sensitivity of photodetectors, despite extensive research in the scientific community over the years, it is only in recent times that this phenomenon has been investigated as a novel technology with potential applications.…”
Section: Introductionmentioning
confidence: 99%